A Mass Spectrometric Approach for Probing the Stability of Bioorganic Radicals1. (20th January 2014) - Tan, Lei; Hu, Hanfeng; Francisco, Joseph S.; Xia, Yu
Abstract Glycyl radicals are important bioorganic radical species involved in enzymatic catalysis. Herein, we demonstrate that the stability of glycyl‐type radicals (X‐.CH‐Y) can be tuned on a molecular level by varying the X and Y substituents and experimentally probed by mass spectrometry. This approach is based on the gas‐phase dissociation of cysteine sulfinyl radical (X‐Cys<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4sm9r5vk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> SO .</alternatives>‐Y) ions through homolysis of a CαCβ bond. This fragmentation produces a glycyl‐type radical upon losing CH2SO, and the degree of this loss is closely tied to the stability of the as‐formed radical. Theoretical calculations indicate that the energy of the CαCβ bond homolysis is predominantly affected by the stability of the glycyl radical product through the captodative effect, rather than that of the parent sulfinyl radical. This finding suggests a novel experimental method to probe the stability of bioorganic radicals, which can potentially broaden our understanding of these important reactive intermediates.